Pengaturan Industri Permainan Interaktif Elektronik di Era Industri 4.0 Video Game Industry Regulation In 4.0. Industry Era - Yoshua Pramana Kawi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
The video game industry has developed very significantly in the 4.0 industry era. Video game industry development also happened in Indonesia in the last two decades, making the government then feel the need to assign a system of regulation to the video game industry in Indonesia. However, a particular part of that said system, which is Regulation of Indonesia’s Esports Major Administrator Number 034/PB-ESI/B/VI/2021, caused some problems regarding its application in public. Therefore, the researcher is interested to study these problems by using the principles of the regulation-making process in the Republic of Indonesia’s Act Number 12 of 2011 and other related law sources. The purpose of this research is to know and understand the regulation of the video game industry and the application’s impact on the public. The research method is using the normative method with the law and conceptual approaches. The result is showing that the development of the video game industry in Indonesia should be controlled in a good regulation system and the implications must be handled seriously by those in charge to provide huge benefits for the country, especially for those working in the video game industry.